Composite outcomes in observational studies of ulcerative colitis: A systematic review and meta‐analysis. Issue 1 (14th December 2021) - Magro, Fernando; Alves, Catarina; Santiago, Mafalda; Ministro, Paula; Lago, Paula; Correia, Luís; Gonçalves, Raquel; Carvalho, Diana; Portela, Francisco; Dias, Cláudia Camila; Dignass, Axel; Danese, Silvio; et al.
Abstract: Background: Ulcerative colitis (UC) has been the focus of numerous observational studies over the years and a common strategy employed in their design is the use of composite and aggregate outcomes. Objective: This systematic review and meta‐analysis aims to identify composite and aggregate outcomes of observational studies in UC and to evaluate how the number and type of variables included and the length of follow‐up affect the frequency of patients that achieve these outcomes. Methods: A systematic literature search was carried out using MEDLINE [via PubMed], Scopus, and Web of Science online databases. Observational studies that included UC patients and reported composite or aggregate outcomes were identified. A set of variables considered to be representative of progressive or disabling UC was defined, the proportion of patients attaining the outcomes was determined and a random‐effects meta‐analysis was performed by dividing the identified studies into subgroups according to different criteria of interest. Results: A total of 10, 264 records were identified in the systematic search, of which 33 were retained for qualitative analysis and 20 were included in the meta‐analysis. The mean frequency for composite outcomes was 0.363 [95% confidence interval (CI) 0.323‐0.403]. The frequency of composite outcome for the subgroup of studies that included the variable "Biologics" was significantly higher than for those in which this variable was not reported [0.410; 95% CI 0.364‐0.457 versus 0.298; 95% CI 0.232‐0.364; p  = 0.006]. Composite outcomes were also more frequent as the follow‐up duration increased. Conclusion: The frequency of composite outcomes in observational studies of UC is dependent on the specific identity of the variables being reported. Moreover, longer follow‐up periods are associated with higher frequencies of composite outcomes. The evidence provided here is useful for the design of future observational studies of UC that aim to maximize the frequency of patients that achieve composite outcomes. Key summary: Summarize the established knowledge on this subject Observational studies have become a valuable source of information but also present a remarkable heterogeneity. The inconsistency on the reported outcomes between individual studies and the potential for reporting biases has led to calls for the development of core outcome sets (COS). What are the significant and/or new findings of this study? This is the first systematic review and meta‐analysis of outcomes in observational studies of Ulcerative colitis (UC). The frequency of composite outcomes in observational studies of UC is dependent on the specific identity of the variables being reported and on the follow‐up duration. Reporting of the variable "Biologics" significantly increased the frequency of composite outcomes. These findings may be useful for the design of future observational studies of UC.